2004
DOI: 10.5694/j.1326-5377.2004.tb06076.x
|View full text |Cite
|
Sign up to set email alerts
|

Achieving better in‐hospital and after‐hospital care of patients with acute cardiac disease

Abstract: In patients hospitalised with acute coronary syndromes (ACS) and congestive heart failure (CHF), evidence suggests opportunities for improving in‐hospital and after‐hospital care, patient self‐care, and hospital–community integration. A multidisciplinary quality improvement program was designed and instigated in Brisbane in October 2000 involving 250 clinicians at three teaching hospitals, 1080 general practitioners (GPs) from five Divisions of General Practice, 1594 patients with ACS and 904 patients with CHF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 10 publications
(14 reference statements)
2
34
0
Order By: Relevance
“…Two interventional studies used medication prescription rates at GP follow-up as a clinical indicator to evaluate programs designed to improve post-ACS care [30, 31]. Hickey et al [30] examined a quality improvement initiative known as the Brisbane Cardiac Consortium (BCC).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two interventional studies used medication prescription rates at GP follow-up as a clinical indicator to evaluate programs designed to improve post-ACS care [30, 31]. Hickey et al [30] examined a quality improvement initiative known as the Brisbane Cardiac Consortium (BCC).…”
Section: Resultsmentioning
confidence: 99%
“…Though the study showed significant improvements in some clinical indicators, it did not report a significant change in prescription rates of medications in primary care follow-up post-intervention ( n  = 89 and n  = 104 for 3- and 6- month follow-up, respectively). Scott et al [31] examined the efficacy of a multi-faceted intervention that included clinical decision support, educational interventions, regular performance feedback, patient self-management strategies, and hospital-community integration. The study found greater prescription rates of aspirin at 3 months post-discharge in intervention patients compared to patients that received usual care ( p  = 0.05), and high rates of aspirin ( p  = 0.03) and β-blocker ( p  = 0.05) continuation among those prescribed these medications at discharge ( n  = 344).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…32,33 Similarly, performance feedback on specific practices has been extensively used in health maintenance organizations for quality improvement, 3438 however, this is not standard practice in health care settings, and information rarely is relayed at the time of a patient visit. Multifaceted interventions, such as PAIR-UP, appear to yield the greatest success in improving asthma care.…”
Section: Discussionmentioning
confidence: 99%